There is no answer other than -8 + 9w - 23p since an algebraic expression in two variables cannot be solved without the values of the two variables.
-9w + zt + wz - 9t = (z - 9)(t + w)
81w2 - p2 = (9w + p) (9w - p)because 81w2 - p2 is the difference of squares. To factor the difference of squares, square root both terms and write the binomial twice:(9w ? p) (9w ? p)Now, to replace the question marks, one binomial has to replace it with the plus sign, while the other binomial gets a minus sign:(9w + p) (9w - p)
It is 23p/1p = 32/1 = 23.
6x-9w = -3
The perimeter of a triangle is the sum of the lengths of the three sides.If the three expressions in the question are in fact the lengths of thethree sides, then the perimeter is their sum.(7x + 9w) + (2x + 8y) + (2y + 5w) = 9x + 10y + 14w
23p.
-9w + zt + wz - 9t = (z - 9)(t + w)
81w2 - p2 = (9w + p) (9w - p)because 81w2 - p2 is the difference of squares. To factor the difference of squares, square root both terms and write the binomial twice:(9w ? p) (9w ? p)Now, to replace the question marks, one binomial has to replace it with the plus sign, while the other binomial gets a minus sign:(9w + p) (9w - p)
56p - 23p = 33
The answer is -4v + 83v^2.
It is 23p/1p = 32/1 = 23.
6x-9w = -3
6 - 9w = 24 -9w = 18w = -2
9w - 3.5 = 1 9w = 4.5 w = 0.5
The perimeter of a triangle is the sum of the lengths of the three sides.If the three expressions in the question are in fact the lengths of thethree sides, then the perimeter is their sum.(7x + 9w) + (2x + 8y) + (2y + 5w) = 9x + 10y + 14w
It is an expression that can be simplified to: -9w-15
It can be simplified to: -1-9w